2012
DOI: 10.1016/j.neuron.2012.06.024
|View full text |Cite
|
Sign up to set email alerts
|

JNK3 Perpetuates Metabolic Stress Induced by Aβ Peptides

Abstract: SUMMARY Although Aβ peptides are causative agents in Alzheimer's disease (AD), the underlying mechanisms are still elusive. We report that Aβ42 induces a translational block by activating AMPK, thereby inhibiting the mTOR pathway. This translational block leads to widespread ER stress, which activates JNK3. JNK3 in turn phosphorylates APP at T668, thereby facilitating its endocytosis and subsequent processing. In support, pharmacologically blocking translation results in a significant increase in Aβ42 in a JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(186 citation statements)
references
References 76 publications
8
177
0
1
Order By: Relevance
“…20 Enhanced JNK3 levels could be linked to Ab-induced endoplasmic reticulum (ER) stress, which has been reported to be increased in Alzheimer disease brains. 14,34 In addition, ER stress is implicated in JNK3 regulation in cellular models. 14 A previous systematic search for global gene expression in Alzheimer disease also showed an increase of JNK cascade cluster in patients in late Braak stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Enhanced JNK3 levels could be linked to Ab-induced endoplasmic reticulum (ER) stress, which has been reported to be increased in Alzheimer disease brains. 14,34 In addition, ER stress is implicated in JNK3 regulation in cellular models. 14 A previous systematic search for global gene expression in Alzheimer disease also showed an increase of JNK cascade cluster in patients in late Braak stages.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous studies implicating JNKs in the pathogenesis of Alzheimer disease have shown that JNKs, particularly JNK3, can phosphorylate APP, enhancing Ab production. 13,14 JNK activity can also raise BACE1 expression 15 and is detected in granulovacuolar degeneration. 16 Activated JNKs are increased in Alzheimer disease brains 17 as well as some upstream JNK activators, such as JKK1.…”
Section: J Psychiatry Neurosci 2015;40(3)mentioning
confidence: 99%
See 1 more Smart Citation
“…JNK activation has been observed in various neurodegenerative disorders where the JNK signaling cascade has been shown to cause neuronal cell death (15)(16)(17)(18)(19). Importantly, postmortem studies, along with MPTP and 6-OHDA animal models of neurodegeneration, showed an important role for JNK in the disease pathogenesis (15,16,19).…”
mentioning
confidence: 99%
“…6 It has been suggested that the toxicity of Aβ is associated with the c-Jun N-terminal kinase (JNK) pathway. 7,8 Cell apoptosis needs extracellular signals to be transmitted to the nucleus, for which the JNK pathway is suggested to be critical. 9 The JNK signaling pathway is one of the important pathways of the mitogen-activated protein kinase (MAPK) family.…”
Section: Introductionmentioning
confidence: 99%